(untitled) (inOpera Esercizi di lettura su testi contemporanei, 2025)
This essay explores the evolution of movement as a theme in Vittorio Sereni’s poetry, tracing the shift from train to automobile as a paradigm of a broader perceptual transformation. From the walking experience in Frontiera to the railway journeys in Diario d’Algeria, to the emergence of the automobile in Gli strumenti umani and Stella variabile, movement functions as a device that reorganizes the relationship between subject, landscape, and memory. The automobile, initially bearer of the «privilege of motion», reveals its limitations in the later collections, signaling the impossibility of achieving authentic memory recovery through speed.